Assessing Factors Influencing Poaching in Majete Wildlife Reserve, Malawi - Martin Gibson Awazi; Maureen Kapute Mzuza (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Poaching is the greatest threat to many of our planet’s most charismatic, valuable, and ecologically important species. Wildlife poaching poses significant threats not only to wildlife conservation and our shared natural heritage but also to security, good governance, and economic development objectives around the globe. This study broadly sought to assess the factors influencing poaching in Majete Wildlife Reserve. The study concluded that poverty, drought and traditional cultures among the local community members had negatively impacted wildlife conservation in Majete Wildlife Reserve. Therefore, the study recommended that the Park Management Unit design projects that meet the needs of the local community members and must also target poachers to increase the buy-in. Furthermore, irrigation projects proved effective in averting hunger caused by persistent drought. Sensitization was also among the effective measure in addressing the problem. As such, it must be intensified to curtail the malpractice. It was also recommended to recruit more rangers to enforce the policing strategies in areas prone to poaching due to the absence of game rangers.